2017
DOI: 10.3389/fimmu.2017.01438
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin in a Context of Inflammation-Induced Pathology

Abstract: Much progress has been achieved to elucidate the function of lactoferrin (LTF), an iron-binding glycoprotein, in the milieu of immune functionality. This review represents a unique examination of LTF toward its importance in physiologic homeostasis as related to development of disease-associated pathology. The immunomodulatory nature of this protein derives from its unique ability to “sense” the immune activation status of an organism and act accordingly. Underlying mechanisms are proposed whereby LTF controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
204
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(218 citation statements)
references
References 137 publications
(161 reference statements)
4
204
0
10
Order By: Relevance
“…Specifically, LF functions as an iron transporter and serves important bacteriostatic and antiviral roles . At sites of inflammation, for example, LF sequesters Fe 3+ and prevents the formation of hydroxyl radicals via the Fenton reaction, which in turn prevents lipid peroxidation from occurring . The protein structure consists of two globular lobes (N‐ and C‐lobes) connected by a three‐turn alpha‐helix .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, LF functions as an iron transporter and serves important bacteriostatic and antiviral roles . At sites of inflammation, for example, LF sequesters Fe 3+ and prevents the formation of hydroxyl radicals via the Fenton reaction, which in turn prevents lipid peroxidation from occurring . The protein structure consists of two globular lobes (N‐ and C‐lobes) connected by a three‐turn alpha‐helix .…”
Section: Introductionmentioning
confidence: 99%
“…Other than the direct modulation of immune response, Lf strategically acts as a potent anti-inflammatory agent by scavenging ROS, pro-oxidant agents able to both promote DNA damage and induce/sustain inflammatory disorders, drastically contributing to cancer development. Lf is able to maintain the physiological balance of ROS levels by either direct binding of free iron, one of the principal actors involved in ROS production, and regulation of key antioxidant enzymes, thus globally protecting host from ROS-mediated cell and tissue damages [192]. In this respect, a recent study by Mohammed and colleagues have shown that bLf significantly down-regulated the activity of liver antioxidant enzymes, namely catalase, glutathione peroxidase, and superoxide dismutase, along with an increase of the concentration of hepatic reduced glutathione, in a murine model of diethylnitrosamine-induced hepatocarcinogenesis.…”
Section: Lactoferrin Anti-cancer Activity: Immunomodulationmentioning
confidence: 99%
“…Лактоферин вважають гострофазовим білком, який функціонує як представник родини алармінів, що вивільняються з нейтрофілів після їх інфікування. Лактоферин бере участь в організації зв'язку між нейтрофілами і дендритними клітинами, стимулюючи перехід від вродженої до адаптивної імунної відповіді [18]. Лактоферин, взаємодіючи з В-лімфоцитами, сприяє антитілоутворенню [27].…”
Section: таблиця 3 динаміка назоцитограми у хворих із гострим простиunclassified